Efficiency in index options markets and trading in stock baskets - Ackert, Lucy F; Tian, Yisong S (Journal of Banking & Finance, 2001)
Researchers have reported mispricing in index options markets. This study further examines the efficiency of the S&P 500 index options market by testing theoretical pricing relationships implied by no-arbitrage conditions. The effect of a traded stock basket, Standard and Poor’s Depository Receipts (SPDRs), on the link between index and options markets is also examined. We find that pricing efficiency within option markets improves but there is little evidence to support the hypothesis that a stock basket enhances arbitrage across markets. When transactions costs and short sales constraints are included, very few violations of inter-market pricing relationships such as put–call parity are reported. However, violations of within market pricing relationships such as the box spread remain frequent. Extensive analysis suggests that the results are robust.